Analisis Kemampuan dan Kinerja Keuangan Daerah di Kota Banjarmasin - Wiguna, Anggi Putra (PPJP ULM, 2018)
This study aims to analyze the condition and financial performance in the city ofBanjarmasin as well as some efforts what has been made by the Government ofBanjarmasin City to improve the ability and financial performance of the region.Results from the study during the period 2011-2016. The annual growth rate of21.34% has been successful in the process of local government, and it looks quite anenormous contribution of Local Revenue to the APBD is 14.12%. The degree of FiscalDecentralization Banjarmasin during the period 2011-2016 is high, with an average of14.12%, said the pattern of a relationship with infective. Meanwhile, the financialperformance of Kota Banjarmasin from the side of fiscal needs is seen to increase duringthe period 2011-2016 average Rp. 313.493.023.747 billion means Fiscal Capacitygreater than Fiscal Requirement. The average capacity of tax capacity is Rp.344.725.786.194 or more. The fiscal position of Banjarmasin City, from the dimension ofUPAD shows strong.